A quick analysis in relation to the electronic commerce of performance- and image-enhancing drugs based on the infrastructure of the world wide web - Lutfi, Ahmed M. (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: Performance- and Image-Enhancing Drugs (PIEDs) refer to all known forms of substances, that can enhance either the morphology or the physiological performance or both simultaneously. The exponential rise of electronic commerce (e-commerce) for PIEDs is a major public issue, for which control protocols are to be deployed.Materials and Methods: It would be a waste of time and resources to track and/or shut down all PIED-promoting websites one by one. Cyberspace is vast; the PIED “product managers” will always adapt to surveillance-control policies over their illegitimate online businesses. A more rational approach would be to track, challenge, and tackle the same resources upon which PIED electronic commerce is based: the infrastructure of the World Wide Web (the Internet).Results: Concerning PIED e-commerce, the main resources are Google and AOL (search engines); YouTube, Wikipedia, and Facebook (social media sites); and Alibaba, Amazon, and eBay (major e-commerce websites).Conclusion: Illegal PIED e-commerce became a major public problem. The major drivers are the Internet search engines, social media sites, and major e-commerce websites. Effective protocols toward these resources would hinder any future progress of this illegitimate worldwide phenomenon.Asian Journal of Medical Sciences Vol.7(4) 2016 88-93